Unlocking Employee Peak Performance on Gen Z: When Organizational Commitment Becomes the Key? - Kurniawan, Iman; Permana Putra, Indradi Tiyas; Damayanti, Devi; Maharani, Anita (Syntax Literate, 2025)
This study explores how employee experience, mental toughness, psychological wellbeing, and work motivation influence organizational commitment and job performance among Generation Z in Indonesia. Drawing on data from the Central Statistics Agency (2020), which indicates Generation Z's dominance in the Indonesian workforce (27.94%), this research adopts a survey design with 330 respondents from the Jabodetabek area. Using the PLS-SEM approach, the study finds that these factors positively and significantly impact organizational commitment. Moreover, organizational commitment mediates the relationship between these variables and job performance. These findings emphasize the importance of nurturing organizational commitment, especially among Generation Z, who seek supportive workplaces promoting psychological wellbeing and offering career growth opportunities. Thus, organizations should devise tailored strategies to foster employee wellbeing, motivation, and commitment for sustainable success.